Mycotoxins: detection methods, management, public health and agricultural trade - Leslie, J. F.; Bandyopadhyay, R.; Bandyopadhyay, R.; Leslie, J. F.; Visconti, A.; Visconti, A. (Wallingford :CABI, 2008)
This book is an outcome of the MycoGlobe conference in Accra. Most of the chapters are based on invited oral presentations made at the conference. The chapters in this book touch on issues including health, trade, ecology, epidemiology, occurrence, detection, management, awareness and policy. This book serves as a source of information on the occurrence and impact of mycotoxins on everything from trade and health to agricultural production in addition to suggesting opportunities for their management in Africa and elsewhere by researchers, policy makers and development investors.
Keywords: EE110 - Agricultural Economics; EE116 - Food Economics, (New March 2000); EE118 - Health Economics, (New March 2000); QQ200 - Food Contamination, Residues and Toxicology; VV820 - Toxinology, (New March 2000); Africa